2022
DOI: 10.1515/bmc-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of genetic markers for identification of the Lr46/Yr29 “slow rusting” locus in wheat (Triticum aestivum L.)

Abstract: Wheat leaf rust, caused by fungal pathogen Puccinia triticina Erikss, annually contributes to production losses as high as 40% in susceptible varieties and remains as one of the most damaging diseases of wheat worldwide. Currently, one of the major challenges of wheat geneticists and breeders is to accumulate major genes for durability of rust resistance called “slow rusting” genes using marker-assisted selection (MAS). Until now, eight genes (Lr34/Yr18, Lr46/Yr29, Lr67/Yr46, Lr68, Lr74, Lr75, Lr77, and Lr78) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Stripe rust resistance gene Yr69 has also been found to be bordered proximally by Xbarc124 (Hou et al 2016). Bobrowska et al (2022) found that Xwmc44 is the appropriate marker for detection of Lr46/Yr29 gene's resistance allele. Similarly, Yr59, an adult plant resistance gene was positioned on the long arm of chromosome 7B, and was tagged by Xbarc32 (Zhou et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stripe rust resistance gene Yr69 has also been found to be bordered proximally by Xbarc124 (Hou et al 2016). Bobrowska et al (2022) found that Xwmc44 is the appropriate marker for detection of Lr46/Yr29 gene's resistance allele. Similarly, Yr59, an adult plant resistance gene was positioned on the long arm of chromosome 7B, and was tagged by Xbarc32 (Zhou et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This gene provides partial broad spectrum resistance against leaf rust and is an ideal target for stacking with other disease resistance genes (Singla et al 2017). Bobrowska et al (2022) has checked the diagnostic accuracy of genetic markers for identification of slow rusting locus in wheat. Functional markers identified in the present study can also be validated using similar course of study.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular markers used successfully identified selected Lr resistance genes in the hybrid forms tested ( Table 2 ). It has been reported in the literature that STS marker csLV34 is highly reliable for Lr34 [ 25 , 33 , 34 ], and csLV46G22 is a highly reliable and close diagnostic marker for the Lr46 gene [ 22 , 27 , 35 ]. In the case of the presence of Lr34 , we obtained a product of 150 bp.…”
Section: Resultsmentioning
confidence: 99%
“…PCR was performed with FastGene Optima HotStart ReadyMix reagents (NIPPON Genetics Europe GmbH, Düren, Germany), using a Labcycler thermal cycler (SensoQuest GmbH, Göttingen, Germany). The composition of the reaction mixture is given in our previous work [ 27 ]. The PCR consisted of initial denaturation at 94 °C for 3 min, followed by 35 cycles (denaturation, 94 °C for 30 s; primer annealing, 60 °C for 30 s; elongation, 72 °C for 90 s), followed by the final extension for 10 min at 72 °C and storage at 4 °C.…”
Section: Methodsmentioning
confidence: 99%